How able sixth form students felt about themselves, about learning and about others : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University - Constable, Cheryl (Massey University, 1994)
In order to investigate how able sixth form students felt about themselves, about learning, and about other people a pilot study was carried out. From an analysis of the findings of the pilot study, a questionnaire was designed which covered relevant affective (social and emotional) domain aspects such as competitiveness, perfectionism, fear, sensitivity, enjoyment, confidence, happiness, defensiveness, security, worry, and choices in what and how the students learned. In order to gain more indepth information about how these students felt about themselves, about learning, and about others, a second source of data was collected. Small groups of students from the questionnaire cohort were interviewed. The interview questions were based on the results from the questionnaire; that is the frequency counts of how many students agreed and disagreed with each of the fifty statements. These interviews gave the students the opportunity to respond to the results of the questionnaire, add a contextual base to their responses in the questionnaire, establish any causal relationships between the topics in the questionnaire, and reduce any researcher bias in the interpretation of the results. The questionnaire sample consisted of 283 students from 20 schools who were nominated by their teachers as able, according to criteria supported in the literature. The interview sample consisted of 46 students from 7 schools. The research aimed to explore how the students felt about themselves and how they described themselves, how they felt about their own learning, how they felt when they were learning with others, and to point to any problems they had in these areas of the affective domain. The results showed that the students perceived they had a lack of confidence; had fears and anxieties; were perfectionists at some things; were competitive in order to remain accepted by their group; wanted to change some things about what and how they learned, especially increasing the amount of discussion; were inexperienced in making choices, especially career goals; felt stressed; wanted more life skills; wanted to combine practical skills with theoretical knowledge to make sense of their experiences; but enjoyed being with others despite worrying about what others thought of them in certain circumstances. The students indicated that these areas adversely affected the quality of their learning.
Keywords: New Zealand; Educational psychology; High school students; Motivation in education